Can't buy me happiness: How voluntary simplicity contributes to subjective wellbeing - Nadime van Dijk (University of Bath, Centre for Development Studies (CDS), 2013)
The ongoing debate on the purpose of 'development' has given rise to many new studies on happiness and quality of life situated in both developed and developing countries. Recent insights from this field include the suggestions that ever-increasing incomes do not always increase happiness, and that an emphasis on materialistic values goes hand in hand with relatively low levels of subjective wellbeing. Meanwhile, key authors within the 'new economics' debate are concerned with the effects of dominant economic values and behaviours on human and ecological wellbeing. They point towards 'voluntary simplicity', a more sustainable practice that involves a relatively low consumption level, as a way forward. While it is clear that lifestyles based in less materialistic pursuits benefit the natural environment, it remains unclear how they may contribute to quality of life. Building forth on recent psychological and other research, this paper combines primary and secondary qualitative data to suggest how voluntary simplicity contributes to subjective wellbeing. Policy makers looking to promote human and ecological wellbeing are advised to make use of an empirically grounded understanding of how relatively ecologically sustainable lifestyles may contribute to life satisfaction.
Keywords: 330; wellbeing; voluntary simplicity; new economics; life satisfaction; simple living